Uji Aktivitas Adaptogenik Ekstrak Etanol Buah Jambu Biji (Psidium guajava L.) pada Mencit Menggunakan Metode Swimming Endurance Test - Pramiastuti , Oktariani; Muzaeni , Doni Wahyu; Istriningsih , Endang (Universitas Borneo Lestari, 2025)
Adaptogenic activity is related to antioxidant activity that can neutralize the adverse effects of stress by reducing the formation of reactive oxygen species (ROS) in the early phase. Psidium guajava has been known to have antioxidant activity, one of which is the highest Vitamin C content in guava fruit among other fruits, strengthening the suspicion that this fruit has adaptogenic activity. This study was conducted with the aim of testing the adaptogenic activity produced from guava fruit using the swimming endurance test (SET) method. Guava fruit extract was produced from the maceration process using 96% ethanol solvent. The SET test was conducted to determine the immobile time in 5 groups of mice that were given orally for 7 consecutive days. CMC-Na 0.5% as a negative control was given to group I, amitriptyline 25 mg/Kg BW as a positive control was given to group II, and extracts with doses of 50, 150 and 250 mg/Kg BW were given to groups III, IV and V, respectively. The results showed adaptogenic activity if the immobilization time of the group given guava fruit ethanol extract was lower than the negative control group. At doses of 50, 150, and 250 mg/Kg BW, the test findings demonstrated that guava fruit ethanol extract was able to shorten the period that mice were immobilized in comparison to the negative control group, indicating that guava fruit ethanol extract has adaptogenic activity. This activity cannot be separated from the role of several groups of compounds, and a few of them are regarded as alkaloids, flavonoids, tannins, saponins, and vitamin C.